The American Leonardo : a Tale of Obsession, Art and Money - Brewer, John, 1947- (Oxford University Press, USA, 2009)
In 1919 a returning World War I veteran named Harry Hahn and his French bride attempted to sell what they thought was a painting by Leonardo Da Vinci in New York. Renowned art dealer Sir Joseph Duveen declared the picture-La Belle Ferronniere-a fake without ever seeing the canvas. The Hahns sued Duveen for slander, setting off a legal battle that would last for decades. In The American Leonardo, John Brewer traces the twisting path of the Hahn La Belle-a painting of famously uncertain origin--as he illuminates the workings of the twentieth-century art market, exploring such larger questions ab.